PENERAPAN GAYA EKSPOSITORI PADA FILM DOKUMENTER COSMIC ENERGY I KETUT BUDIANA - Suardewanti, Ni Kadek Asri; Puriartha, I Kadek; Putra, Ida Bagus Hari Kayana (CALACCITRA: JURNAL FILM DAN TELEVISI, 2025)
Documentary films are a development according to non-fiction films where documentary films contain information & contain the subjectivity of the makers. This means that what is recorded is based on existing facts (Nugroho, 2007). According to Chandra Tansil (2010:5), the stages of making a documentary film are divided into six parts, namely Building ideas, Research, Composing a storyline, Composing production design, Filming, Editing images and sound on the editing table. Expository Documentary Films or Documentaries that focus on presenting facts and information with clear and objective narratives. Expository documentaries are one type of documentary film that aims to convey information, facts, or knowledge to the audience objectively and informatively. The production of the documentary film "Cosmic Energy I Ketut Budiana" raises the story of artist I Ketut Budiana which shows how the creative process of artist I Ketut Budiana in creating his work where the artist explores the basic concepts of cosmos life, namely concepts that are actually universal, born from the appreciation of Balinese spiritual values. This documentary aims to show the results of cultural art works created by a maestro who is very creative and innovative in his work. The process of creating the documentary film “Cosmic Energy I Ketut Budiana” involved partners and supervising lecturers who have helped to create a work that has continued benefits until the work is quickly completed.